The Influence of Service Quality and Customer Trust on Customer Satisfaction at Bank Bengkulu Bintuhan Branch - Hasbullah Hasbullah; Karona Cahya Susena; Suswati Nasution (Jurnal Fokus Manajemen, 2022)
The purpose of this study is to find out how the influence of service quality and customer trust on customer satisfaction at Bank Bengkulu Branch Bintuhan. The data collection method used a questionnaire and the data analysis method used was the multiple linear regression analysis method using the SPSS program. The results of this study are the quality of service has a significant effect on the customer satisfaction variable of Bank Bengkulu Branch Bintuhan as indicated by the value of tcount > ttable (2.716> 1.66071) and a significant value < (0.05) (0.020 <0.05). For the customer trust variable, the tcount value is 2.221 and the ttable value is 1.66071 with a significance level of 5% with two directions, the tcount>ttable (2.221>1.66071) and the significant value < (0.05) (0.015<0 ,05). Simultaneously service quality and customer trust have a significant effect on customer satisfaction at Bank Bengkulu Branch Bintuhan, this can be seen from the results of the F test, namely F count > F table (14,863 > 3,090) or a significant value of 0.000 < 0.05. .